PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN WISATAWAN YANG MENGINAP DI SIESTA LEGIAN HOTEL (Studi Pada Wisatawan yang Menginap di Siesta Legian Hotel) - Komang Sintia Meliani; Ni Luh Putu Agustini K. (Journal Research of Management, 2020)
The purpose of this study was to analyze the effect partially and simultaneously between the marketing mix consisting of product, price, place, promotion, process, people, physical evidence variables towards the satisfaction of tourists who stayed at Siesta Legian Hotel. The analysis used is multiple linear regression and beta coefficients. The sample in this study were tourists who stayed at Siesta Legian Hotel, which amounted to 102 people. The sampling technique used was purposive sampling and quantitative analysis. Based on the results of data analysis, it can be seen that the partial effect of the product on tourist satisfaction is 42.3%, the price is 52.4%, the distribution channel is 53.8%, promotion is 43.8%, the process is 41.8%, people are 65.8% and the dominant variable is physical evidence with a value of 44.2% which indicates that the placement of rooms and and the atmosphere of the lobby has the value of the dominant variable. The coefficient of determination results or R2 shows the number 0.775, which means that as many as 77.5% of the marketing mix variables affect the satisfaction of tourists who stay at the Siesta Legian Hotel, while as many as 22.5% of tourist satisfaction staying at Siesta Legian Hotel is influenced by other variables. The conclusion of this study is that the marketing mix has a significant effect on the satisfaction of tourists who stay at Siesta Legian Hotel. The implications of this study are to provide benefits for hotels to pay more attention to the marketing mix used to increase the satisfaction of tourists who stay at Siesta Legian Hotel.